The impact of PROGRESA on women's status and intrahousehold relations: final report - Adato, Michelle; de la Briere, Benedicte; Mindek, Dubravka; Quisumbing, Agnes R. (International Food Policy Research Institute, 2000)
The objective of this report to examine the impact of PROGRESA on women’s status and intrahousehold relations. The program provides cash benefits linked to children’s school attendance and to regular clinic attendance, as well as in-kind health benefits and nutritional supplements. Unlike previous social programs in Mexico, a unique feature of this nationwide anti-poverty program is its targeting of transfers to the mother of the family. The deliberate decision to give transfers directly to the mother was motivated by the growing literature which finds that resources controlled by women are more likely to be manifested in greater improvements in child health and nutrition than resources controlled by men. Program staff also argue that the design of the program may increase women’s “empowerment” by increasing their control over resources and thus their bargaining power. This report takes a two-prong approach to analyzing the impact of PROGRESA on women’s status and intrahousehold relations, using both quantitative survey data and qualitative focus group studies. It is composed of two separate and complementary papers. The first paper, by Bénédicte de la Brière and Agnes Quisumbing, uses the data from the quantitative surveys—the Survey of Socio-Economic Characteristics of Households (ENCASEH) and three successive Evaluation Surveys (ENCEL)—to examine three aspects of intrahousehold relations: how family background of husband and wife influences the human and physical capital they bring to marriage; how husband’s and wife’s resources at the time of marriage affect household decisionmaking patterns; and how parental characteristics affect the relative schooling achievements of boys and girls. The second paper, by Michelle Adato and Dubravka Mindek, is based on qualitative research methods that allowed beneficiaries, non-beneficiaries and promotoras to explain their experience of PROGRESA in their own words. Using the lens of women’s “empowerment,” this paper focuses primarily on the perspectives of beneficiaries and promotoras with regard to changes they perceive in their lives, related directly and indirectly to features of the program. Exploring the assumptions that the central role played by women in PROGRESA has both benefits and unintended consequences; and that women’s and men’s attitudes and beliefs have implications for the success of the program, this study examines: women’s and men’s attitudes toward the role of women as PROGRESA beneficiaries; the perceived benefits to the household as well as increased tensions and time burdens; decisionmaking patterns; changes women describe with regard to freedom of movement, self-confidence, and ‘opening their minds;’ women’s and men’s attitudes toward the education of girls, adult education that women want for themselves in order to improve their lives, and education they want for men to help women put into practice what they learn through participation in the program.